Parental Knowledge and Oral Health Maintenance in Kindergarten Children: A Study at UPTD Ulak Rengas Health Center, 2025 - Jihan Salsabila; Syiefa Renanda Surya; Febria Listina (PROMOTOR, 2026)
Dental and oral health problems in children, such as dental caries, can cause toothache that disrupts sleep and concentration, impair chewing ability which reduces nutritional intake, and potentially affect cognitive and psychomotor development. According to the Indonesian Health Survey (SKI, 2023), the prevalence of dental caries among children aged 3–4 years is 81.1%, among those aged 5–9 years is 92.6%, and among those aged 10–14 years is 73.4%. Preliminary survey results indicated that most kindergarten children experience dental and oral health problems. This study aims to examine the relationship between parents’ knowledge and the maintenance of dental and oral health in kindergarten children in the working area of UPTD Ulak Rengas Public Health Center, North Lampung, in 2025. This is a quantitative study with a cross-sectional design. The sample consisted of 59 parents, selected using proportional random sampling. Data were collected using a questionnaire. The frequency distribution test results showed that 19 respondents (32.2%) had poor dental health maintenance, while 40 respondents (67.8%) had good dental health maintenance. The chi-square statistical test revealed a significant relationship between knowledge (p-value = 0.007; OR = 5.815) and dental health maintenance. It is recommended that the public health center strengthen regular and scheduled dental and oral health education and counseling programs for the community through posyandu (integrated health service posts), schools, and other community activities.